Analisis Kerjasama Amerika Serikat-Indonesia dalam Menurunkan Emisi Gas Rumah Kaca Melalui Program FOLU Net Sink 2030 - Rauf, Mutmainnah; Luneto, Riska; Amsir, Achmad Abdi (UIN Alauddin Makassar, 2025)
In order to address the challenges of climate change, international cooperation is essential, especially for large countries that contribute significantly to greenhouse gas emissions. The United States is the second largest producer of greenhouse gas emissions in the world after China, and Indonesia is the largest producer of greenhouse gas emissions in Southeast Asia. Therefore, through the FOLU Net Sink 2030 program, the two countries have formed a partnership to reduce greenhouse gas emissions from the forestry and land use sectors, which can absorb emissions of -140 million tons of CO2e. The objective of this study is to examine initiatives to reduce greenhouse gas emissions through cooperation between the United States and Indonesia through the FOLU Net Sink 2030 program. This study employs qualitative research methods, specifically library research, supplemented by theories of international cooperation and green politics theory. The findings indicate that the collaboration between the United States and Indonesia through the FOLU Net Sink 2030 program began in 2022, with data showing a reduction in greenhouse gas emissions in the FOLU sector of 8.15 million tons of CO2e in 2022, in 2023, there was a fivefold decrease from the previous year, amounting to 37.77 million tons of CO2e, and in 2024, a decrease of 42.6 million tons of CO2e. The general conclusion of this study is that cooperation between the United States and Indonesia is important because it can promote low-carbon development in Indonesia nationally and serve as an international cooperation strategy to achieve global climate targets.